Effect of Ultrasonic Treatment on the Quality of Pumpkin Juice Fermented by Yeast - Wenhui Pan; Wen Li; Chunli Zhou; Manjun Zhang; Wei Su; Renqin Tan; Leyi Yao (Foods, 2025)
To investigate the effect of ultrasound on the quality of pumpkin juice fermented by yeast, ultrasound (power range 0–400 W, duration 10 min) was used to assist the yeast fermentation of pumpkin juice. The effects of ultrasound-assisted fermentation at different powers on the quality characteristics of pumpkin juice, such as the color, aroma components, carotenoid content, and antioxidant activity, were studied. The optimal combination of fermentation process parameters was determined as follows: a pumpkin juice content of 20 mL, fermentation temperature of 30 °C, fermentation time of 1 day, and inoculation amount of 3% (the mass-to-volume ratio of yeast to water). The results showed that after ultrasound treatment, the physicochemical properties of pumpkin juice, including the Vitamin C (VC) content, carotenoid content, and antioxidant activity, did not change significantly (p > 0.05), while the total acid content decreased significantly, indicating that ultrasound treatment was beneficial for improving the sensory properties of pumpkin juice after yeast fermentation. Notably, when the ultrasound power was 100 W, the flavonoid content in pumpkin juice reached the highest level (1.27 mg/100 g). A total of 127 volatile substances were identified via gas chromatography, among which 14 were characteristic aroma profiles of pumpkin juice, suggesting that ultrasound (US) treatment had little impact on the natural flavor of pumpkin juice. Cavitation caused cell rupture in pumpkin juice, and ultrasound treatment significantly improved the sterilization rate of yeast-fermented pumpkin juice and was extremely effective in maintaining its color. This study provides a theoretical basis for the development of high-quality and nutrient-rich fermented pumpkin juice.